1 V Tunable High-Quality Universal Filter Using Multiple-Input Operational Transconductance Amplifiers - Kumngern, Montree; Khateb, Fabian; Kulej, Tomasz; Knobnob, Boonying (MDPI, 2024)
This paper presents a new multiple-input single-output voltage-mode universal filter employing four multiple-input operational transconductance amplifiers (MI-OTAs) and three grounded capacitors suitable for low-voltage low-frequency applications. The quality factor (Q) of the filter functions can be tuned by both the capacitance ratio and the transconductance ratio. The multiple inputs of the OTA are realized using the bulk-driven multiple-input MOS transistor technique. The MI-OTA-based filter can also offer many filtering functions without additional circuitry requirements, such as an inverting amplifier to generate an inverted input signal. The proposed filter can simultaneously realize low-pass, high-pass, band-pass, band-stop, and all-pass responses, covering both non-inverting and inverting transfer functions in a single topology. The natural frequency and the quality factors of all the filtering functions can be controlled independently. The natural frequency can also be electronically controlled by tuning the transconductances of the OTAs. The proposed filter uses a 1 V supply voltage, consumes 120 mu W of power for a 5 mu A setting current, offers 40 dB of dynamic range and has a third intermodulation distortion of -43.6 dB. The performances of the proposed circuit were simulated using a 0.18 mu m TSMC CMOS process in the Cadence Virtuoso System Design Platform to confirm the performance of the topology.

This paper presents a new multiple-input single-output voltage-mode universal filter employing four multiple-input operational transconductance amplifiers (MI-OTAs) and three grounded capacitors suitable for low-voltage low-frequency applications. The quality factor (Q) of the filter functions can be tuned by both the capacitance ratio and the transconductance ratio. The multiple inputs of the OTA are realized using the bulk-driven multiple-input MOS transistor technique. The MI-OTA-based filter can also offer many filtering functions without additional circuitry requirements, such as an inverting amplifier to generate an inverted input signal. The proposed filter can simultaneously realize low-pass, high-pass, band-pass, band-stop, and all-pass responses, covering both non-inverting and inverting transfer functions in a single topology. The natural frequency and the quality factors of all the filtering functions can be controlled independently. The natural frequency can also be electronically controlled by tuning the transconductances of the OTAs. The proposed filter uses a 1 V supply voltage, consumes 120 mu W of power for a 5 mu A setting current, offers 40 dB of dynamic range and has a third intermodulation distortion of -43.6 dB. The performances of the proposed circuit were simulated using a 0.18 mu m TSMC CMOS process in the Cadence Virtuoso System Design Platform to confirm the performance of the topology.
1 V Tunable High-Quality Universal Filter Using Multiple-Input Operational Transconductance Amplifiers
Keywords: universal filter; voltage-mode circuit; operational transconductance amplifier; universal filter; voltage-mode circuit; operational transconductance amplifier